TURIZMO SEKTORIAUS RAIŠKOS PAGRINDIMAS: VADYBINIO IR EKONOMINIO KONCEPTO PAIEŠKOS = JUSTIFICATION OF THE TOURISM SECTOR MANIFESTATION: SEARCHING FOR MANAGERIAL AND ECONOMIC CONCEPT - Asta Valackienė; Rasa Glinskienė (Taikomieji tyrimai studijose ir praktikoje, 2018)
The article deals with the development and trends of the tourism sector as a branch of economy. The managerial and economic concept of the sector's expression is revealed. The authors of the article refer to the theoretical insight, which conceptualises the concepts of hospitality and hospitality business, in support of the managerial aspect of the tourism sector. When discussing the economic aspect of the tourism sector, it was based on the method of secondary statistical data: analysis of strategic documents regulating the intensive development of tourism in Europe and Lithuania, taking into account Lithuania social and economic development tendencies. According to data provided by the World Tourism Organization (WTO), the tourism sector was exported in 2016. The revealed management and economic concept of the tourism sector has allowed expanding the field of social phenomenon analysis. The management concept was highlighted in the discussion of the tourism sector, in which two values of the concept of hospitality as a branch of tourism were revealed. In the first case, the most prominent aspect of the tourism sector is that of hospitality, presented as a provision or feature that is expressed by the generous, friendly and benevolent acceptance (accommodation) of guests, visitors or clients and catering to all the wishes and wishes of their guests, ensuring that guests would be satisfied, feel good and would like to come back. This concept reflects the competencies of people working in the tourism sector and the main factors determining the changes in the behavior of tourism services users. In the second case, it has been established that hospitality in the tourism sector appears as a business area in which professional activities are directed towards participants of the tourism sector as users of hospitality services - for tourists, for the local population. It should be noted that both of these concepts are based on qualitative criteria for the services provided in the tourism sector. It can be argued that in interpreting the economic concept of tourism as a segment of the economy it is necessary to assess the socio-economic conditions of globalization. In recent years, the ever-changing tendencies of economic, political, demographic, social, technological, and cultural development in the world have been observed: growing population of people, changing lifestyles, improving livelihoods, technological advances contributes to the competitiveness of the development of the tourism sector and investment prospects in the market. It has been determined that methodologically, based on the hospitality management paradigm and the analysis of the methodology of strategic documents regulating tourism, the trends of development and expression of the tourism sector as a branch of economy are revealed in Lithuania. An overview of strategic documents, which presents the objectives focused on the expression of the tourism sector, developing both the management (professional development of employee competence, etc.), both macro and micro economic (aspects of a competitive environment, search for new markets, etc.).